Governance, efficiency and risk taking in Chinese banking - Dong, Yizhe; Girardone, Claudia; Kuo, Jing-Ming (The British accounting review, 2017)
We employ a hand-collected unique dataset on banks operating in China between 2003 and 2011 to investigate the impact of board governance features (size, composition and functioning) on bank efficiency and risk taking. Our evidence suggests that board characteristics tend to have a greater influence on banks' profit and cost efficiency than on loan quality. We find that the proportion of female directors on the board appears not only to be linked to higher profit and cost efficiency but also to lower traditional banking risk. Similarly, board independence is associated with higher profit efficiency of banks; while the opposite is found for executive directors and in the presence of dual leadership of the CEO/chairperson. Among the control variables, we found that liquidity negatively affects profit and cost efficiency, while positively affecting risk. Interestingly, we find some evidence of an incremental effect of specific board characteristics on efficiency for banks with more concentrated ownership structures and state-owned institutions; while for banks with CEO performance-related pay schemes the effect on efficiency when significant is usually negative. Our results offer useful insights to policy makers in China charged with the task of improving the governance mechanisms in banking institutions.